Toxic epidermal necrolysis caused by over the counter eyedrops. (17th August 2012) - Byrom, Lisa; Zappala, Tania; Muir, Jim
Abstract We present a case of a 15‐year‐old boy who developed toxic epidermal necrolysis (TEN) from sulfacetamide eyedrops. He presented with conjunctival injection and an erythematous rash that rapidly progressed to epidermal necrosis of over 30% of his body. A skin biopsy revealed an acute lichenoid reaction pattern consistent with TEN. After 22 days in hospital, he was left with significant scarring to his eyes, mouth and anogenital areas. An extensive search for an infective aetiology was negative. Previously exposed to bactrim tablets, he used Bleph‐10 eyedrops 3 days before admission to hospital. The patient had a strong family history of sulphur allergy. The onset of TEN after topical administration of medication has been reported rarely in the literature. This case highlights the need for a thorough medication history that includes topical preparations.